Multiscale modeling of vertebrate limb development. (24th March 2020) - Glimm, Tilmann; Bhat, Ramray; Newman, Stuart A.
Abstract: We review the current state of mathematical modeling of cartilage pattern formation in vertebrate limbs. We place emphasis on several reaction–diffusion type models that have been proposed in the last few years. These models are grounded in more detailed knowledge of the relevant regulatory processes than previous ones but generally refer to different molecular aspects of these processes. Considering these models in light of comparative phylogenomics permits framing of hypotheses on the evolutionary order of appearance of the respective mechanisms and their roles in the fin‐to‐limb transition. This article is categorized under: Analytical and Computational Methods > Computational Methods Models of Systems Properties and Processes > Mechanistic Models Developmental Biology > Developmental Processes in Health and Disease Analytical and Computational Methods > Analytical Methods Abstract : Drawings (left) and simulations (right) of experimentally manipulated (ZPA graft; chicken) (top), and mutant (Shh‐/‐Gli3‐/‐; mouse) (bottom) embryonic limbs.